Morfologia de sementes e de estádios iniciais de plântulas de espécies de Bromeliaceae da Amazônia - Silva, Ivone Vieira; Scatena, Vera Lúcia [UNESP] (My University, 2011)
Seeds of Aechmea bromeliifolia, A. castelnavii (Bromelioideae); Dyckia duckei, D. racemosa (Pitcairnioideae) and Tillandsia adpressiflora (Tillandsioideae) were collected in the Amazon regions (Mato Grosso) and studied to describe morphological characterization and post-seminal development, which can be taxonomically useful, and to assess percent germination. All the species have epigeous germination and produce cryptocotyledonary plantlets. Seeds have no dormancy and percent germination is high (over 86%), which facilitates the production of seedlings and conservation studies. Exclusive characteristics of the genera include: the seed coat of Aechmea (Bromelioideae) has mucilage that prevents desiccation; whereas that of Dyckia (Pitcairnioideae) has membranaceous wings and that of Tillandsia (Tillandsioideae) has feathery appendages, both of which make dispersal easier and establish the epiphytic habit. Initial post-seminal development of Aechmea (Bromelioideae) and Dyckia (Pitcairnioideae) is marked by the emergence of primary roots, interpreted as a basal character, whereas that of Tillandsia adpressiflora (Tillandsioideae) is marked by the emergence of the cotyledon, interpreted as a derived character. Dyckia and Tillandsia have a small tank only in the seedling phase while the contrary occurs in Aechmea.
Seed morphology and early seedling stages in Bromeliaceae from the Amazon
Keywords: Aechmea; Dyckia; Germination; Seed; Tillandsia; Aechmea bromeliifolia; Bromeliaceae; Cotyledon (genus)